IMPLEMENTASI PENDEKATAN PEMBELAJARAN CULTURALLY RESPONSIVE TEACHING (CRT) PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI KEBERAGAMAN SOSIAL BUDAYA KELAS IV SD NEGERI BUGANGAN 03 - Ero Susanti; Harto Nuroso; Istichomah; Arfilia Wijayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to demonstrate and explain the extent to which students are engaged in acquiring Pancasila education through the application of the Culturally Responsive Teaching (CRT) paradigm. Research data was gathered by processes including observation, interviews, and documentation. The three components of data analysis are data transfer, data reduction, and conclusion drawing. The protocols in question were adhered to when teaching content concerning social and cultural diversity utilizing the CRT approach model. Applying the Culturally Responsive Teaching (CRT) approach model, according to observational findings, raised student learning activity levels in all domains, including task completion, question-asking, answering, and lesson following, which all increased by 26%, 22%, and 36%, respectively. The use of the CRT strategy in class IV D SDN Bugangan 03 yields positive results since it can enhance student learning activities in the Pancasila Education learning process on socio-cultural diversity material.